2015
DOI: 10.1044/2015_jslhr-s-13-0250
|View full text |Cite
|
Sign up to set email alerts
|

Vowel Space Characteristics of Speech Directed to Children With and Without Hearing Loss

Abstract: Purpose: This study examined vowel characteristics in adult-directed (AD) and infant-directed (ID) speech to children with hearing impairment who received cochlear implants or hearing aids compared with speech to children with normal hearing. Method: Mothers' AD and ID speech to children with cochlear implants (Study 1, n = 20) or hearing aids (Study 2, n = 11) was compared with mothers' speech to controls matched on age and hearing experience. The first and second formants of vowels /i/, /ɑ/, and /u/ were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 55 publications
(138 reference statements)
4
41
0
Order By: Relevance
“…Fourth, infants with CIs displayed IDS preference similar to their hearing experience-matched peers, rather than their chronological age-matched peers. These may be largely related to the nature of the input because caregivers seemed to adjust their speech styles according to the hearing and developmental status of their infants with hearing impairment, rather than the chronological age (Bergeson et al, 2006;Wieland, Burnham, Kondaurova, Bergeson, & Dilley, 2015). For example, the increase in average and minimum pitch from ADS to IDS in mothers' speech to infants with CIs was more similar to that in speech to the control infants with matched hearing experience and distinct from control infants with matched chronological age (Bergeson et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Fourth, infants with CIs displayed IDS preference similar to their hearing experience-matched peers, rather than their chronological age-matched peers. These may be largely related to the nature of the input because caregivers seemed to adjust their speech styles according to the hearing and developmental status of their infants with hearing impairment, rather than the chronological age (Bergeson et al, 2006;Wieland, Burnham, Kondaurova, Bergeson, & Dilley, 2015). For example, the increase in average and minimum pitch from ADS to IDS in mothers' speech to infants with CIs was more similar to that in speech to the control infants with matched hearing experience and distinct from control infants with matched chronological age (Bergeson et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…This agrees with previous literature that shows maternal speech to HI infants is affected by infant hearing loss (Chen, 1996;Cheskin, 1981;Cross, JohnsonMorris, & Nienhuys, 1980;Kondaurova & Bergeson, 2011;Kondaurova et al, 2012;Kondaurova, Bergeson, & Kitamura, 2013;Kondaurova, Bergeson, & Xu, 2013;Kondaurova et al, 2015;Kondaurova, Blank, Zheng, Abu Zhaya, & Seidl, 2016;Nienhuys, Cross, & Horsborough, 1984;Wieland, Burnham, Kondaurova, Bergeson, & Dilley, 2015). Previous research has demonstrated that mothers use shorter utterances, exaggerated pitch characteristics, and a slower speaking rate when interacting with their HI infants (Kondaurova, Bergeson, & Xu, 2013).…”
Section: Infant and Mother Vocalizationssupporting
confidence: 82%
“…However, studies explicitly investigating VHH in IDS across development generally report no differences between ages. This is the case regardless of whether they find overall hyperarticulation in IDS compared to in ADS (Liu et al, 2009;Cristia and Seidl, 2014;Wieland et al, 2015;Hartman et al, 2017;, overall hypoarticulation in IDS compared to in ADS (Englund and Behne, 2006;Benders, 2013) or no difference in VHH between IDS and ADS (Xu Rattanasone et al, 2013;Burnham et al, 2015;Wieland et al, 2015).…”
Section: Vhh In Ids As a Function Of Infant Agementioning
confidence: 92%
“…Hyperarticulated IDS has been reported for ages between 3.1 months (Kuhl et al, 1997) and 63 months (Liu et al, 2009; not within range in Figure 1), and hypoarticulated IDS has been reported for ages between 0.9 months (Englund and Behne, 2006) and 15.3 months (Benders, 2013). Ages for which no difference in VHH between IDS and ADS has been found span 3.0 months to 20.4 months (Dodane and Al-Tamimi, 2007;Kondaurova et al, 2012;Xu Rattanasone et al, 2013;Burnham et al, 2015;Wieland et al, 2015;.…”
Section: Vhh In Ids As a Function Of Infant Agementioning
confidence: 97%